Strain detection in non-magnetic steel by Kerr-microscopy of magnetic tracer layers - Jourdan, Martin; Kraemer, M. M. B.; Klaeui, M.; Elmers, H-J; Deldar, S.; Smaga, Marek; Beck, T. (Journal of Magnetism and Magnetic Materials, 2018)
For many applications of steel, e.g. for the evaluation of the fatigue state of components or structures, the characterization of the microscopic strain distribution in the material is important. We present a proof-of-principle for the visualization of such strain distributions by Kerr-microscopy of ferromagnetic tracer layers on nonmagnetic steel sheets. The influence of indentation induced strain on the magnetic domain pattern of 20 nm Galfenol and Permalloy tracer layers on austenitic AISI 904L steel sheets was investigated. The obtained Kerr-microscopy images show a characteristic domain pattern in the strained regions of the steel sheets, which is consistent with a dominant magneto-elastic contribution to the domain pattern formation.
CRIS-Team Scopus Importer:2023-03-27